The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Nouvelle encyclopédie politique et historique des femmes - Fauré, Christine (Les Belles Lettres, 2010)
Comment les femmes ont-elles perdu en France le pouvoir de gouverner? Pourquoi Calvin s'est-il excusé auprès de la reine d'Angleterre Élisabeth Ie lorsqu'elle accéda au trône? Comment les femmes ont-elles participé collectivement aux Révolutions anglaises du XVIIe siècle, américaine, française, liégeoise et brabançonne, néerlandaises du XVIIIe siècle? Quelles ont été les formes de résistance des femmes esclaves dans la traite négrière? Comment les utopistes et les marxistes ont-ils conçu l'émancipation des femmes? Quand le féminisme est-il né? Comment a-t-il évolué? Quand et comment les femmes ont-elles obtenu le droit de vote dans les États européens, en Amérique du Nord, en Amérique latine? Savez-vous que des femmes s'enrôlèrent dans le nazisme, le fascisme italien, la collaboration française, le franquisme, le salazarisme portugais? Quelle fut l'action souvent méconnue des résistantes à ces régimes totalitaires? La Commune de Paris de 1871, les Révolutions russes de 1905 et 1917, la Révolution allemande de 1918 ont-elles marqué des avancées sociales et politiques pour les femmes? Quelles ont été la liberté et l'égalité pour les femmes dans les pays du communisme réel? Qui étaient Clara Zetkin, Rosa Luxemburg et Alexandra Kollontaï? Qu'est-ce que les deux Guerres mondiales ont changé pour les femmes? Quelle est l'étendue du succès politique des femmes dans les pays nordiques? Comment des femmes ont-elles combattu les dictatures militaires d'Amérique latine? Comment les mouvements de libération des femmes des années 1970 ont-ils traversé l'Atlantique? Comment la mondialisation affecte-t-elle les relations hommes- femmes? Comment les organisations internationales ont-elles construit, idéalement, l'égalité entre femmes et hommes?
Keywords: amériques; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; his4330; histoire des femmes*; histoire et politique; militance; outils; ouvrages de références; participation citoyenne; premier cycle; régions géographiques; science politique; science politique et droit; thématiques

Emotions and social movements - Flam, Helena; King, Debra (Routledge, 2005)
Addressing issues of emotion in social movements, this internationally oriented volume will appeal to both sociologists and political activists given its broad approach and unique emphasis on emotions in protest, dissent and social movements.
Keywords: 1900-1999; care; discipline; militance; mouvements sociaux; outils; ouvrages de références; périodes historiques; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions